Wilcox's surgical anatomy of the heart - Anderson, Robert H. 1942- (Cambridge University Press, 2024)
This classic textbook on cardiac anatomy has been updated in its fifth edition with additional high quality surgical and pathological photographs, as well as new information and recent findings of the last decade. Beginning with an overview of surgical approaches to the heart, the book goes on to discuss the surgical anatomy of the cardiac chambers, the valves, and the circulation and conduction system within the heart, moving on to cover malformations, lesions, and abnormalities. This edition is informed by the most up-to-date research findings, and a new chapter has been added which reviews cardiac development. A complimentary digital companion now accompanies the book, allowing readers to view the images in high-resolution on screen. Written from the stance of the cardiac surgeon, this updated book is essential reading for consultants and trainees in cardiac surgery, cardiology and cardiovascular radiology, and anatomists.